Pengaruh Aerobic Low Impact Exercise terhadap Fungsi Kognitif Lansia dengan Risiko Demensia di Sasana Tresna Werdha Cibubur Tahun 2025 - Achirda, Nur; Liza Laela Abida; Kania Annisa Zahra (Jurnal Fisioterapi Terapan Indonesia, 2025)
Background: Entering old age, the elderly often face various problems, one of which is impaired cognitive function. Some factors that influence the decline in cognitive abilities in the elderly include gender, education level, occupation, nutritional status, and comorbidities that can interfere with the nervous system, such as dementia and Alzheimer's disease. The problem of dementia in the elderly is an important concern that requires effective prevention and treatment. Dementia in the elderly can include several aspects, such as orientation, registration, attention and calculation, memory, and language. Physiotherapy has an important role in maintaining and improving body movement function, so that a person can remain active independently. Aerobic physical activity can activate the hypothalamus to synthesize corticotropin-releasing factor (CRF), which will affect the release of neurotransmitters such as acetylcholine, serotonin, dopamine, and norepinephrine that improve memory consolidation. Objective: To determine the effect of aerobic low impact exercise on changes in cognitive function in the elderly with risk factors for dementia at STW Ria Pembangunan Cibubur. Methods: This study used a pre-experimental method with a one group pre-test and post-test approach. A total of 12 people who have met the inclusion and exclusion criteria. The measuring instrument used was MMSE. The intervention was carried out 2 times a week for 4 weeks. Results: From all research objects, the average result of cognitive function before intervention was 17.00 and after intervention was 19.67. Hypothesis testing shows there is an effect of Aerobic Low Impact Exercise on improving cognitive function. Conclusion: Aerobic Low Impact Exercise has an effect on improving cognitive function in elderly people with dementia risk at STW Ria Pembangunan Cibubur.